Studies on directly grown few layer graphene processed using tape-peeling method. (March 2020) - Yang, Junha; Kumar, Sunil; Kim, Minwook; Hong, Hyeryeon; Akhtar, Imtisal; Rehman, Malik Abdul; Lee, Naesung; Park, Jun-Young; Kim, Ki Buem; Seo, Yongho
Abstract: We have developed a novel way to fabricate few layers graphene by controlling the uniformity of graphene using 'tape-peeling' method to solve the problem in the direct growth method based on the polymer carbon source. This method increases uniformity of the directly grown graphene by removing large amounts of residues during graphene direct growth using tape-peeling, and it can help in controlling the thickness of graphene. For the direct growth of graphene, nickel (Ni) was deposited on the silicon dioxide (SiO2 ) substrate, and poly (methylmethacrylate) was used as a carbon source. During the annealing process in the chemical vapor deposition (CVD) technique, a few layer graphene is grown between the Ni and the SiO2 substrate. The Ni is removed by etching using iron (III) chloride (FeCl3 ), but thick carbon residues are left on the substrate. These residues are removed, and the overall thickness of graphene, to some extent, is controlled by the tape-peeling method. It has been found that the tape-peeling method is effective in removing the residues on the sample surface. The directly grown graphene processed by tape-peeling was used in fabricating the photoelectric devices and the corresponding studies have been performed. Graphical abstract: Image 1